Effect of sliding speed and counterface properties on the tribo-oxidation of brush seal material under dry sliding conditions. (April 2016) - Thakare, M.R.; Mason, J.F.; Owen, A.K.; Gillespie, D.R.H.; Wilkinson, A.J.; Franceschini, G.
Abstract: The performance of dynamic seals and hence the overall efficiency of the gas turbine is strongly dependent on the wear of individual seal elements and their ability to provide continuous sealing. Dynamic seals such as brush seals contact the rotating 'rotor' during operation, either transiently or continuously depending on factors such as thermal expansions, axial/radial displacements and eccentricities of the rotating components. This intermittent or continuous contact results in sliding wear of the seal tips and dictates the seal degradation and hence its efficiency. The present work examines the effect of sliding speeds between 6 m s −1 and 150 m s -1 on the wear-oxidation of Haynes 25 brush seal 'tufts' sliding against nitrided steel and thermal sprayed chrome oxide coating. Highlights: Wear characteristics strongly Q3 depend on ability of surfaces to form tribo-films. Stable tribo-film depends on the availability and sinterability of the wear debris. Thermal behaviour is dominated by frictionally generated heat. Sub-surface recrystallisation suggests near-melting temperature at interface. Thermal effects of dry-sliding wear limited to a few microns from the wear interface.